Transforming criminal justice?: problem-solving and court specialization - Donoghue, Jane (Routledge frontiers of criminal justice, 2014)
Situating problem-solving, punitivism and punishment -- Specialist and problem-solving courts -- Drug courts and domestic violence courts -- Community courts and mental health courts -- Neighbourhood justice panels -- Problem-solving and court specialization : prospects and pitfalls